1993
DOI: 10.1002/pola.1993.080311120
|View full text |Cite
|
Sign up to set email alerts
|

Living carbocationic polymerization of isobutyl vinyl ether and the synthesis of poly[isobutylene‐b‐(isobutyl vinyl ether)]

Abstract: SYNOPSISThe MeCH (0-i-Bu) C1/TiC14/MeCONMe2 initiating system was found to induce the rapid living carbocationic polymerization ( LC@Pzn) of isobutyl vinyl ether ( IBuVE) at -100°C. Degradation by dealcoholation which usually accompanies the polymerization of alkyl vinyl ethers by strong Lewis acids is "frozen out" at this low temperature and poly (isobutyl vinyl ether)s (PIBuVEs) with theoretical molecular weights up to ca. 40,000 g/mol (calculated from the initiator/ monomer input) and narrow molecular weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…On the other hand, a catalytic amount of some strong bases such as amides and dimethyl sulfoxide (DMSO) induces living cationic polymerization of isobutene using BCl 3 or TiCl 4 , as reported by Kennedy and coworkers 6. However, these base‐stabilized living polymerization systems were limited to some combinations containing a monomer, an added base, and a Lewis acid 4–14. Recently, we found that SnCl 4 induces living cationic polymerization of amide‐containing vinyl ethers in the presence of an ester.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…On the other hand, a catalytic amount of some strong bases such as amides and dimethyl sulfoxide (DMSO) induces living cationic polymerization of isobutene using BCl 3 or TiCl 4 , as reported by Kennedy and coworkers 6. However, these base‐stabilized living polymerization systems were limited to some combinations containing a monomer, an added base, and a Lewis acid 4–14. Recently, we found that SnCl 4 induces living cationic polymerization of amide‐containing vinyl ethers in the presence of an ester.…”
Section: Introductionmentioning
confidence: 91%
“…6 However, these base-stabilized living polymerization systems were limited to some combinations containing a monomer, an added base, and a Lewis acid. [4][5][6][7][8][9][10][11][12][13][14] Recently, we found that SnCl 4 induces living cationic polymerization of amide-containing vinyl ethers in the presence of an ester. Considering this background, we decided to examine cationic polymerization in the presence of a strong Lewis base, such as an amide or an amine.…”
Section: Introductionmentioning
confidence: 99%
“…The living cationic polymerization of vinyl ethers requires the use of weak Lewis acids such as iodine and zinc chloride, while that of isobutylene necessitates strong Lewis acids such as titanium(IV) chloride and boron chloride. Thus, the living poly(vinyl ether) cannot initiate the polymerization of IB, and the introduction of vinyl ethers to living PIB reaction mixtures leads to low crossover efficiency, as was the case of isobutyl vinyl ether (IBVE), due to an unfavorable ratio of crossover rate over propagation rate ( R c / R p ). To increase the crossover efficiency from less reactive monomers to more reactive monomers, attempts have been made by lowering the Lewis acidity or adding common ion salts. , These attempts failed, since the decrease in R p was inevitably accompanied by the decrease of R c .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the living poly(vinyl ether) cannot initiate the polymerization of IB, and the introduction of vinyl ethers to living PIB reaction mixtures leads to low crossover efficiency, as was the case of isobutyl vinyl ether (IBVE), due to an unfavorable ratio of crossover rate over propagation rate ( R c / R p ). To increase the crossover efficiency from less reactive monomers to more reactive monomers, attempts have been made by lowering the Lewis acidity or adding common ion salts. , These attempts failed, since the decrease in R p was inevitably accompanied by the decrease of R c . To increase the crossover efficiency, the ratio of R c / R p should be increased.…”
Section: Introductionmentioning
confidence: 99%
“…While PSt-PIB-PSt with excellent mechanical properties was obtained using sequential monomer addition,1 the crossover efficiency was found to be low from the PIB living end to p-methylstyrene (pMeSt),8 and even lower to aMeSt12 or isobutyl vinyl ether. 13 We invented a novel strategy for the synthesis of block copolymers by sequential monomer addition when the second monomer is more reactive than the first one. The strategy was used for the synthesis of PIB-PpMeSt diblock or PpMeSt-PIB-PpMeSt triblock copolymers.…”
Section: Introductionmentioning
confidence: 99%